2004
DOI: 10.3161/00159301ff2004.47.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Maro sublestus Falconer, 1915 (Araneae, Linyphiidae) - a species new to the fauna of Poland

Abstract: F r a g m e n t a F a u n i s t i c a 4 7 (2 ): In t r o d u c t i o n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…These were three Maro species (Linyphiidae), i.e. M. lehtineni Saaristo, 1971(Wiśniewski & Wesołowska 2015, M. lepidus Casemir, 1961(Wiśniewski & Wesołowska 2012), M. sublestus Falconer, 1915 (Szymkowiak 2004) and Iberina difficilis (Harm, 1966) from Hahniidae (Wiśniewski et al 2013). In this article we present four other spider species from the region, which are new to the fauna of Poland.…”
Section: Introductionmentioning
confidence: 99%
“…These were three Maro species (Linyphiidae), i.e. M. lehtineni Saaristo, 1971(Wiśniewski & Wesołowska 2015, M. lepidus Casemir, 1961(Wiśniewski & Wesołowska 2012), M. sublestus Falconer, 1915 (Szymkowiak 2004) and Iberina difficilis (Harm, 1966) from Hahniidae (Wiśniewski et al 2013). In this article we present four other spider species from the region, which are new to the fauna of Poland.…”
Section: Introductionmentioning
confidence: 99%
“…M. minutus was also found together with M. lepidus -in addition to the above-mentioned bog -on one mire in the Izera valley. M. sublestus was reported from Poland only in Western Sudety Mountains (Szymkowiak 2004, Kupryjanowicz 2008. In the present study 5 specimens of this species were identified.…”
Section: H a R A C T E R I S T I C H A B It A T Smentioning
confidence: 99%